PENERAPAN DISCOVERY LEARNING DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR ILMIAH SISWA SD - Widiya (ADISAM PUBLISHER, 2026)
Natural Science (IPA) learning in elementary school is very important in helping students develop scientific thinking skills from an early stage. However, teacher-centered instruction often makes students less motivated to explore and understand concepts independently. This study aims to explain how the Discovery Learning model is implemented in science instruction to improve the scientific thinking skills of elementary school students. The Discovery Learning model focuses on enabling students to discover concepts on their own through various activities such as observing, classifying, asking questions, formulating hypotheses (temporary assumptions), and drawing conclusions independently. This model encourages students to be more enthusiastic in exploring learning materials, enhances their curiosity, and trains them to think logically and critically. The study indicates that the use of the Discovery Learning method in science learning helps students more easily identify problems, formulate simple assumptions, think logically, and draw structured conclusions. Therefore, this model can effectively support the development of scientific thinking skills among elementary school students in an optimal way.